(untitled) (Global Journal of Medical Research, 2023)
The structure of liquid water is more than 50% clusters of solid ice imbedded in liquid water, which makes the water inhomogeneous and with hysteresis properties. Hysteresis means the water history is important, it is a volt-ampere characteristic of the water different when the, voltage is increased and when the voltage is decreased. It means that the increasing voltage has changed the water structure and these changes were still present when the voltage was decreased. Recent studies of Luc Montagnier, who took Nobel Prize for the DNA of the HIV virus, found that when the water with the HIV virus was so diluted that the DNA of the HIV virus was no longer present, the water still had detrimental effect because the frequencies of the DNA of HIVvirus were imprinted on the water structure. Similar were the result of the French immunologist Benveniste, who found that the biological effect of anti-bodies was still present when the water solution was so diluted that anti-bodies were no longer there. When the water is chlorinated to kill the germs in it, the frequencies of the toxic chlorine remain imprinted on the water even when the water is filtered and the chlorine is not any longer there. Considering this, we must stop chlorinating the water. In Germany, years ago Shauberg blew a whistle that chlorinated water did cause cancer and Germany switched to ozonated water. This is the right way to go.